Maternal dietary diversity (MDD-W) in Dibrugarh district, Assam - Saikia, Mridushman; Mahanta, Tulika Goswami; Nirmolia, Nabanita; Nath, Arpita; Saikia, Hiranya; Gogoi, Gourangie (Indian Journal of Community Health, 2024)
Background: (Minimum Dietary Diversity for Women) MDD-W is crucial for both mothers and children, but significant disparities are present. The study was conducted to assess the factors influencing MDD-W among postnatal women of 15-49 years in Dibrugarh, Assam. Methodology: A cross-sectional study was carried out with 180 postnatal women using multi-stage sampling and interviewed using 24-hour recall method. Descriptive data was presented as proportions and frequencies, and analysed using Chi-square test and Fisher's exact test. Results: Lack of knowledge on dietary diversity was 77.8%. Only 55.6% consumed foods from ? 5 food groups. Women from rural residences, lower socio-economic status, and late antenatal visits were less likely, while women with higher education, family support were more likely to have MDD-W. Conclusion: Lack of diverse diets, particularly protein and vitamin A-rich foods, among postnatal women necessitates intervention to combat malnutrition.